The Emerging Drugs Network of Australia: A toxicosurveillance system of illicit and emerging drugs in the emergency department. (12th August 2021) - Smith, Jennifer L; Soderstrom, Jessamine; Dawson, Andrew; Alfred, Sam; Greene, Shaun; Isoardi, Katherine; McCutcheon, David; Oosthuizen, Francois; Ezard, Nadine; Burcham, Jonathon; Fatovich, Daniel M; ,
Abstract: Objective: The unprecedented rise in synthetic drugs, many containing unknown toxic agents, has made timely analytical diagnosis more difficult, and has reduced the confidence of clinicians providing ED management to this population of patients. This has also impacted the quality of evidence informing harm reduction responses. The Emerging Drugs Network of Australia (EDNA) brings together emergency physicians, toxicologists and forensic laboratories to establish a standardised ED toxicosurveillance system in Australia. Methods: Blood analysis of intoxicated patients will be conducted by forensic laboratories to enable precise identification of the substances causing acute toxicity. This will be linked with clinical data collected at the time of ED presentation to enable analysis of the clinical effects and outcomes associated with different illicit and emerging drugs. Toxicological and clinical data collected across sentinel sites will align with a nationally endorsed minimum dataset. Results: EDNA's collaborative network will establish a national system of surveillance and reporting of illicit and emerging drugs causing acute toxicity. Standardisation of data collection recorded in a national clinical registry will provide more robust data on epidemiology and associated harms. This will facilitate the translation of clinical and toxicological evidence into timely, appropriate harm reduction and policy. Conclusion: Our work represents a collaborative response to calls for more sophisticated data on emerging drug trends in Australia. EDNA will improve coordination between clinicians and analytical services by way of its standardised approach to surveillance and reporting. Abstract : The Emerging Drugs Network of Australia (EDNA) brings together emergency physicians, toxicologists and forensic laboratories to establish a standardised ED toxicosurveillance system in Australia. Standardisation of data collection recorded in a national clinical registry will provide more robust data on epidemiology and associated harms. This will facilitate the translation of clinical and toxicological evidence into timely, appropriate harm reduction and policy.